Inclusión de las personas con capacidades especiales y su incidencia en el desempeño laboral en el Gobierno Autónomo Descentralizado Municipal del cantón Valencia, provincia Los Ríos, año 2015 - Barragán Zamora, Priscila Antonia (2015)
The study on the care and treatment of persons with special needs in the business sector has been thorough and very important for this reason one must know the impact on job performance as it is an issue that has been taken into account because the commotion in their insertion in international organizations at the level of both public and private, is very noticeable that the entry of this part of the population does not generate as would normally make him, as these people have skills, abilities and knowledge as all. Lack of confidence is perceived in the municipal Gobierno Autónomo Descentralizado of Valencia as the working performance of Features is a visible obstacle to both heads of areas and for people with special needs, and that because of that there are areas where They do not have sufficient confidence in the accuracy of their results, are located in other areas where their activities are however not according to their capabilities. In the methodological part are methods, techniques and tools used in this investigation were the same as central to the project. Also it was concluded and recommended based on the results of surveys conducted administrative staff with disabilities in the municipal decentralized autonomous government of Valencia Canton. Keywords: Inclusion; Features; job performance; work environment; disability; decentralized local self-government.